The concept of zuhud based on fiqh al-hadith / Mohammad Fahmi Abdul Hamid, Ishak Suliaman and Mohd Farhan Md Ariffin - Abdul Hamid, Mohammad Fahmi; Suliaman, Ishak; Md Ariffin, Mohd Farhan (Universiti Teknologi MARA, Perlis, 2016)
Zuhud in mysticism is a discipline aimed for better quality of lifestyle. The true concept of Zuhud is a modest style of living. Therefore, practitioners of mysticism need to emphasize Zuhud in their life. However, problems occur when practisioners do not implement the true concept of Zuhud in mysticism. This article elaborates on the concept of Zuhud according to al-Kitab al-Zuhud which is based on al-Kuttub al-Sittah. Using the qualitative and quantitative analysis, there were 555 hadith in the Kitab al-Zuhud based on al-Kuttub al-Sittah. 421 were hadith sahih, 53 da’if, 41 hasan, 21 hasan sahih, 11 da’if jiddan, 4 sahih lighairih, 2 mawdu’ and 2 munkar. As a conclusion, the true concept of Zuhud based on fiqh al-Hadith consists wealth and live, deeds, speeches, foods, earnings, wara’ tawadu’, redha, and be content.